Back to the prairie : a home remade, a life rediscovered - Gilbert, Melissa, 1964- (Gallery Books, 2022)
"The New York Times bestselling author and star of Little House on the Prairie returns with a new memoir -- both hilarious and heartfelt -- chronicling her journey from Hollywood to a ramshackle house in the Catskills during the COVID-19 pandemic. Known for her childhood role as Laura Ingalls Wilder on the classic NBC television show Little House on the Prairie, Melissa Gilbert has spent nearly her entire life in Hollywood. From Dancing with the Stars to a turn in politics, she has always been on the lookout for her next project. She just had no idea that her latest one would be completely life-changing. When her husband introduces her to the wilds of rural Michigan, Melissa begins to fall back in love with nature. And when work takes them to New York, they find a rustic cottage in the Catskills to call home. But 'rustic' is a generous description for the state of the house, which requires a lot of blood, sweat, and tears from the newlyweds to make it habitable. Then the coronavirus pandemic descends upon the world, further nudging Melissa out of the spotlight and into the woods. She trades Botox treatments for DIY projects, power-lunching for gardening and raising chickens, and soon her life is once again rediscovered, in her own little house in the mountains." --